Community Structure of Zooplanktonic Groups of Chimdi Lake, Sunsari, Nepal - Surana, R.; Subba, B.R.; Limbu, K.P. (Our Nature, 2006)
Community structure of zooplankton in Chimdi Lake was assessed during the year 2003-2005. During the period of investigation 15 species of zooplanktons representing 3 groups namely Rotifera, Copepoda and Cladocera were recorded. Key words: Birju Tal, Chimdi Lake, Zooplankton doi:10.3126/on.v3i1.339 Our Nature (2005) 3: 81-82